PENGARUH KARAKTERISTIK PEKERJAAN TERHADAP TURNOVER INTENTION PADA BEBERAPA RESTORAN MASAKAN ORIENTAL DI KOTA SURABAYA - Tony Susilo Wibowo; I Made Bagus Dwiarta (Fakultas Ekonomi dan Bisnis, 2015)
Culinary industry competition getting tougher to make some employers continue to innovate at a restaurant for some things like menu, places, atmosphere and service that became the mainstay of the restaurant. In so doing, it needs one innovation ability of human resources quality and competence in their field. Innovation will be a reminder for consumers who feel the restaurant services and in turn will increase the revenue thus achieved profit restaurant that is optimal.The selected researchers research object was 3rd Restaurant Oriental cuisine i.e. Kapin, X O Cuisine and Paradise Dynasty which respectively have 3 and 2 branches of the restaurant. This research uses the concept of job characteristics expressed by Hackman and Oldham (1976), which are further subdivided into 5 independent variables namely a diversity of tasks, task identity, task meaningful, autonomy and feedback as well as the dependent variable turnover intention, while the analysis on research using multiple linear regression with the respondent an amount of 120 people that consists of all the employees of the restaurant. Data processing results shows that the diversity of the variable assignments and most influential task ID with a value of beta X1 0,676 and the beta X 2 of 0,538 so that these two variables have a positive and significant impact on the turnover intention because the variable is greater than 0.05 alpha. While the 3 other variables i.e tasks meaningful, autonomy and feedback does not affect significantly to turnover intention. Keywords: Job Characteristics, Turnover intention.